2016
DOI: 10.3758/s13414-016-1224-2
|View full text |Cite
|
Sign up to set email alerts
|

Using transcranial direct-current stimulation (tDCS) to understand cognitive processing

Abstract: Noninvasive brain stimulation methods are becoming increasingly common tools in the kit of the cognitive scientist. In particular, transcranial direct-current stimulation (tDCS) is showing great promise as a tool to causally manipulate the brain and understand how information is processed. The popularity of this method of brain stimulation is based on the fact that it is safe, inexpensive, its effects are long lasting, and you can increase the likelihood that neurons will fire near one electrode and decrease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 99 publications
1
82
0
2
Order By: Relevance
“…Against this trend, among the other articles, we must emphasize that only six studies translated these improvements into standardized cognitive assessments (Ferrucci et al, 2008 ; Khedr et al, 2014 ; André et al, 2016 ; Bystad et al, 2016b ; Yun et al, 2016 ; Ladenbauer et al, 2017 ) while other studies reporting improvements in non-standardized CT to prove the effects of tDCS. Yet it must be acknowledged that certain cognitive functions are mediated by networks of various brain sites and might be difficult to be influenced by targeting only a subset of their brain regions (Reinhart et al, 2017 ), besides the short length of the intervention might have contributed to these changes being insufficient to translate into standardized test results.…”
Section: Discussionmentioning
confidence: 99%
“…Against this trend, among the other articles, we must emphasize that only six studies translated these improvements into standardized cognitive assessments (Ferrucci et al, 2008 ; Khedr et al, 2014 ; André et al, 2016 ; Bystad et al, 2016b ; Yun et al, 2016 ; Ladenbauer et al, 2017 ) while other studies reporting improvements in non-standardized CT to prove the effects of tDCS. Yet it must be acknowledged that certain cognitive functions are mediated by networks of various brain sites and might be difficult to be influenced by targeting only a subset of their brain regions (Reinhart et al, 2017 ), besides the short length of the intervention might have contributed to these changes being insufficient to translate into standardized test results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inspecting the influence of tDCS on the posterior occipital area, Sczesny-Kaiser et al ( 2016 ) found an improvement in learning in a phosphene thresholds task, Costa et al ( 2012 ) demonstrated enhanced chromatic contrast sensitivity, and Olma et al ( 2011 ) revealed an improvement in orientation sensitivity. Moreover, a recent study performed by Reinhart et al ( 2017 ) showed a significant improvement in visual hyperacuity, measured with Vernier stimuli. Relying on these demonstrations of improved neural processing as a result of anodal stimulation to posterior occiput, the current study examined whether this technique would also improve visual acuity measured with a Landolt gap task.…”
Section: Introductionmentioning
confidence: 91%
“…Relying on findings of Yeshurun and Carrasco ( 1999 ) and Montagna et al ( 2009 ), we expected to reproduce the attentional effects on visual acuity. Additionally, given previous tDCS findings (Antal et al, 2003 ; Olma et al, 2011 ; Costa et al, 2012 ; Sczesny-Kaiser et al, 2016 ; and Reinhart et al, 2017 ) we hypothesized that anodal tDCS to the occipital area will improve visual processing during stimulation. Finally, combining attentional allocation with tDCS we postulated that the anodal stimulation may modulate the effects of cueing, influencing the effectiveness of spatial attention.…”
Section: Introductionmentioning
confidence: 95%
“…Last, differently from most recent tDCS studies (Clarke et al, 2014;Heeren et al, 2015), we employed an off-line stimulation protocol allowing our participants to perform the task without worries about sensations like tingling or itching under the electrodes. As a previous study (Reinhart & Woodman, 2014) demonstrated that 20-minute tDCS at 1.5 mA intensity over the medial-frontal cortex can affect behavior and brain activity up to 5 hours, we could be confident that our stimulation determined an effect lasting until the end of our task (for a review, see Reinhart, Cosman, Fukuda, & Woodman, 2017).…”
Section: Discussionmentioning
confidence: 79%